2017
DOI: 10.1002/gcc.22481
|View full text |Cite
|
Sign up to set email alerts
|

The co‐regulatory networks of tumor suppressor genes, oncogenes, and miRNAs in colorectal cancer

Abstract: Tumor suppressor genes (TSGs) and oncogenes (OG) are involved in carcinogenesis. MiRNAs also contribute to cellular pathways leading to cancer. We use data from 217 colorectal cancer (CRC) cases to evaluate differences in TSGs and OGs expression between paired CRC and normal mucosa and evaluate how TSGs and OGs are associated with miRNAs. Gene expression data from RNA‐Seq and miRNA expression data from Agilent Human miRNA Microarray V19.0 were used. We focus on genes most strongly associated with CRC (fold cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 61 publications
6
48
0
Order By: Relevance
“…Another study illustrated that elevated PTPN3 expression promotes tumor recurrence and is detrimental to the prognosis of intrahepatic cholangiocarcinoma patients (28). Consistent with our results, Slattery ML et al (29) reported that PTPN11 expression is upregulated in CRC. PTPN11 was also suggested to impact the tumorigenesis and metastasis of CRC (30) and termed as a potential prognostic marker (31).…”
Section: Discussionsupporting
confidence: 91%
“…Another study illustrated that elevated PTPN3 expression promotes tumor recurrence and is detrimental to the prognosis of intrahepatic cholangiocarcinoma patients (28). Consistent with our results, Slattery ML et al (29) reported that PTPN11 expression is upregulated in CRC. PTPN11 was also suggested to impact the tumorigenesis and metastasis of CRC (30) and termed as a potential prognostic marker (31).…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, more and more studies have proved that miRNAs play important roles in a variety of cancer progression, such as respiratory cancers [4], digestive system cancers [5,6], neurological system cancers [7], genitourinary cancers [8] and vascular cancers [9]. miRNAs regulate the proliferation, differentiation, invasion, apoptosis and metastasis process of cancer cells in the form of oncogenes or tumor suppressor genes [10,11].It is worth noting that miRNAs and their target mRNA play synergistic network roles in cancer progression, and the analyses of miRNA expressions have identified potential markers for the diagnosis, prognosis and treatment of cancer patients [12,13].In these respects, more and more studies have confirmed…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that the abnormal expression was related to many human disease and especially in tumours formation and development . SOX9 is over‐expressed in various cancers, such as colorectal cancer, prostate cancer, pancreatic cancer, lung cancer, brain cancer, and melanoma …”
Section: Introductionmentioning
confidence: 99%